Typescript of Diarmuid Lynch’s comments on R. M. Fox’s 'The History of the Irish Citizen Army' and 'Green Banners', - Lynch, Diarmuid, 1878-1950 (1946)
Two copies, one bound, one loose, with foreword signed by Lynch. Includes manuscript annotations, identical for 'Citizen Army' but different for 'Green banners', the one in the bound copy is the "edited version", the other is a "copy for FO'D". Published in 'The IRB and the 1916 Insurrection'. The third item is a mounted collection of 4 newspaper cuttings.